Fungi in the healthy human gastrointestinal tract - Hallen-Adams, Heather E.; Suhr, Mallory J. (Virulence, 2017)
Many species of fungi have been detected in the healthy human gut; however, nearly half of all taxa reported have only been found in one sample or one study. Fungi capable of growing in and colonizing the gut are limited to a small number of species, mostly Candida yeasts and yeasts in the family Dipodascaceae (Galactomyces, Geotrichum, Saprochaete). Malassezia and the filamentous fungus Cladosporium are potential colonizers; more work is needed to clarify their role. Other commonly-detected fungi come from the diet or environment but either cannot or do not colonize (Penicillium and Debaryomyces species, which are common on fermented foods but cannot grow at human body temperature), while still others have dietary or environmental sources (Saccharomyces cerevisiae, a fermentation agent and sometime probiotic; Aspergillus species, ubiquitous molds) yet are likely to impact gut ecology. The gut mycobiome appears less stable than the bacterial microbiome, and is likely subject to environmental factors.